2010
DOI: 10.1093/carcin/bgq143
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol decreases the levels of miR-155 by upregulating miR-663, a microRNA targeting JunB and JunD

Abstract: An inflammatory component is present in the microenvironment of most neoplastic tissues, including those not causally related to an obvious inflammatory process. Several microRNAs, and especially miR-155, play an essential role in both the innate and adaptative immune response. Resveratrol (trans-3,4',5-trihydroxystilbene) is a natural antioxidant with anti-inflammatory properties that is currently at the stage of preclinical studies for human cancer prevention. Here, we establish that, in human THP-1 monocyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
206
1
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(219 citation statements)
references
References 45 publications
7
206
1
5
Order By: Relevance
“…In these cells, resveratrol improved the action of adenosine analogues to inhibit methylation and to increase expression of the retinoic acid receptor beta 2 gene (Stefanska et al 2010). In addition, resveratrol decreased the levels of the miR-155 by up-regulating miR-663, an miRNA targeting JunB and JunD (Tili et al 2010a), and modulated expression levels of miRNA target genes, such as tumor suppressors and effectors of the transforming growth factor-b signaling pathway, in SW480 cells (Tili et al 2010b).…”
Section: Effect Of Other Natural Compounds On Epigeneticsmentioning
confidence: 98%
“…In these cells, resveratrol improved the action of adenosine analogues to inhibit methylation and to increase expression of the retinoic acid receptor beta 2 gene (Stefanska et al 2010). In addition, resveratrol decreased the levels of the miR-155 by up-regulating miR-663, an miRNA targeting JunB and JunD (Tili et al 2010a), and modulated expression levels of miRNA target genes, such as tumor suppressors and effectors of the transforming growth factor-b signaling pathway, in SW480 cells (Tili et al 2010b).…”
Section: Effect Of Other Natural Compounds On Epigeneticsmentioning
confidence: 98%
“…It is upregulated by oscillatory shear stress and has a key role in oscillatory shear-induced inflammatory responses by mediating the expression of the inflammatory gene network in human umbilical vein endothelial cells (Ni et al, 2011). In human THP-1 monocytic cells and human blood monocytes, resveratrol upregulates miR-663, which decreases endogenous activator protein-1 activity and impairs its upregulation by lipopolysaccharides by targeting Jun B and Jun D (Tili et al, 2010a). Furthermore, it is involved in a resveratrolrelevant pathway by targeting transforming growth factor-b1 (Tili et al, 2010b).…”
Section: Introductionmentioning
confidence: 99%
“…The results obtained in the present study showed that wortmannin induces expression of miRs and thus acts as suppresser of tumor growth. It has been reported that miRs exhibits anti-carcinoma effect on tumor growth by interfering with the expression of Jun B and Jun D [19]. miR 19 suppresses the expression of tissue factor which is involved in the progress of tumors [20].…”
Section: Discussionmentioning
confidence: 99%